Analisis Pola Bakteri dan Faktor Risiko Bakteremia pada Unit Perawatan Intensif Dewasa di Rumah Sakit Umum Soeradji Tirtonegoro Klaten, Indonesia: Penelitian - Imma Irfani, Qonita (PT Kalbe Farma Tbk., 2026)
Introduction: Bloodstream infections (BSI) are life-threatening and pose an increased risk of mortality, particularly in intensive care patients. This study aims to delineate the bacterial patterns and analyze the risk factors associated with bacteremia among patients in the adultintensive care unit at Soeradji Tirtonegoro Hospital. Methods: This study used a descriptive-analytical design with a cross-sectional approach. The study population consisted of all adult ICU patients at Soeradji Tirtonegoro Hospital with positive blood cultures during the treatment period from October 1, 2019, to August 31, 2022. Analysis of risk factors associated with bacteremia was performed using Fisher's exact test. Results: Analysis shows a significant association between the accumulation of 3 or more risk factors and the bacterial patterns found in patients with bacteremia. Data from 52 patients were selected for analysis, comprising 21 females and 31 males. The risk factors associated with bacteremia included installation of hemodialysis catheters, water-sealed drainage (WSD), ventilator use, a history of diabetes, and previous surgery. Several patients had more than one risk factor associated with bacteremia. Blood culture results revealed that 30 out of 52 cases (57.7%) were caused by Gram-negative bacteria, while 22 out of 52 cases (42.3%) were caused by Gram-positive bacteria. The analysis identified two cases of methicillin-resistant coagulase-negative staphylococci (MR CoNS), but no methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamases (ESBLs) or carbapenemase-producing bacteria were found. Conclusion: This study identified bacterial patterns and analyzed risk factors associated with bacteremia in adult intensive care units. There was a significant association between the number of accumulated risk factors and specific bacterial pathogens in patients with bacteremia.